Do Tourism and Renewable Energy Influence CO2 Emissions in Tourism-Dependent Countries? - Zebo Kuldasheva; Maaz Ahmad; Raufhon Salahodjaev; Mochammad Fahlevi (International Journal of Energy Economics and Policy, 2023)
The global community gathered in 2015 in Paris to join efforts in order to mitigate the impact of global warming by decreasing carbon emissions. As tourism is viewed as one of the essential causes of global warming, policymakers are searching for tools to decrease the carbon footprint of the tourism sector by introducing energy efficiency strategies. This study aims to contribute to the energy-emissions debate by accounting for the presence of the tourism sector. In particular, we offer novel evidence on the effect of renewable energy on CO2 emissions in a sample of 50 most tourism-oriented countries over the period from 2000 to 2015. Using a two-step GMM estimator, we find that a one percent increase in renewable energy consumption leads to a one percent decrease in CO2 emissions. We also confirm the presence of the Environmental Kuznets Curve phenomena in tourism-oriented countries. Based on the empirical findings, the study suggests that the policymakers of the top tourist-oriented countries initiate more renewable energy-based activities to achieve sustainable economic development.